ANALISIS YURIDIS PENOLAKAN DISPENSASI KAWIN ANAK DI BAWAH UMUR DI PENGADILAN AGAMA SAMPANG - Sayyedi, Moh.; Sutrisno, H. (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
holding weddings for people under one year old. It often causes various problems in married life, such as quarrels between husband and wife and misunderstandings which can hinder the achievement of marriage goals. In other words, the objectives of Islamic law may not be in line with the practice of underage marriage. In this critical situation, the Sampang Religious Court Judge as the holder of full authority must determine which is better: giving the child the opportunity to complete his education or respecting the parents’ wishes to marry the underage child. Finding out whether the judge’s decision, thinking and legal basis in the application for marriage dispensation is relevant to this research is very important.This field research is descriptive in nature. Even though they are only in junior high school, the prospective bride and groom have prepared thoroughly for marriage. The panel of judges at the Sampang Religious Court who tried this case is the subject of investigation. In-depth interviews and written notes formed the basis of this research’s data collection methods. When analyzing technical data, a qualitative descriptive approach is usually used. Article 7 paragraph (1) of Law of the Republic of Indonesia Number 1 of 1974 and Article 53 paragraph (1) of the KHI are the main considerations for the Panel of Judges at the Sampang Religious Court. This is in accordance with Islamic law because it does not conflict with the main principles of Islam.